Experimental investigation of the distinct effects of nanoparticles addition and urea-SCR after-treatment system on NOx emissions in a blended-biodiesel fueled internal combustion engine. (15th February 2020) - Mehregan, Mina; Moghiman, Mohammad
Abstract: The present study reports an investigation about the distinct effects of nanoparticles addition and urea-SCR system on NOx emissions. Also nano-additives influence on pollutants (NOx and CO) reduction performance of a urea-SCR system is investigated. B20 blended biodiesel which contains of 20% waste frying oil biodiesel and 80% diesel has been used as the base fuel in this work. Manganese oxide and cobalt oxide nanoparticles with the mass fractions of 25 and 50 ppm were dispersed in the base fuel as nano-fuel additives. The findings showed that both studied nano-additives reduce NOx emissions. However, the reduction level is lower compared to urea-SCR system. As well as, the results revealed that the pollutants reduction efficiency of the urea-SCR system was appreciably enhanced due to nanoparticles addition.